2012
DOI: 10.1007/s00192-012-1834-8
|View full text |Cite
|
Sign up to set email alerts
|

Bulking agents: an analysis of 500 cases and review of the literature

Abstract: Introduction and hypothesis Stress urinary incontinence (SUI) is common, impacts women's quality of life, and generates high costs. Physiotherapy is the first-line therapy, and if it fails, suburethral slings are the gold standard in SUI surgery. Bulking agents injected periurethrally might be a beneficial alternative, but there is a paucity of data on bulking therapy. The aim of this study was to prospectively analyze the efficacy and safety of bulking agents in the setting of a tertiary referral center. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 48 publications
3
24
0
3
Order By: Relevance
“…However, there is lack and inconsistency of data comparing the outcomes of these agents; therefore, a decision to be made on selecting a bulking agent to treat SUI would be made depending on the availability, safety, ease of use, and surgeons preference [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there is lack and inconsistency of data comparing the outcomes of these agents; therefore, a decision to be made on selecting a bulking agent to treat SUI would be made depending on the availability, safety, ease of use, and surgeons preference [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…This study also showed 0 % complication rate with PAHG. Moreover, this study had a study design different from our systematic review and was a case series [28]. Finally, a sixth study was excluded because it evaluated only the impact of PAHG on the sexual function outcome of women with urinary incontinence [29].…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Bulking agent injection for SUI is simple, safe, and effective . Temporary BOO after injection is common, and BOO usually resolved within hours to days .…”
Section: Managementmentioning
confidence: 99%